Indoor Air Fine Particular Pollution In Ulaanbaatar, Mongolia - B, Buyantushig.; G, Jargalsaikhan.; M, Nansalmaa.; G, Enkhjargal. (Caucasus Journal of Health Sciences and Public Health, 2020)
Indoor air pollution is a major public health problem since people spend most of their lives in indoors. Indoor air pollutants vary depends on many factors, including climate, human activity, season, heating, and fuel consumption. There is a need to examine how the concentration of fine particulate matter or the main indoor air pollutant, fluctuates 24 hours a day concerning fuel combustion, and whether it varies depending on the type of dwelling, compared with previous studies.